Financial Feasibility Analysis of Processing Tumpi on The Home Industry Scale in The Sub-District Kulisusu Utara, North Buton Utara Regency - Sahrim, Sahrim; Rianda, La; Herdhiansyah, Dhian (Tekper : Jurnal Teknologi dan Manajemen Industri Pertanian, 2020)
This study aims to determine the manufacturing process and the financial feasibility of pile processing. This research was conducted in Kulisusu District, North Buton Regency. The population in this study were all business owners of pile processing. The determination of the sample is done by purposive (direct appointment) because the pedicab processing business actor only consists of two business units. Samples taken are as many as two business units consisting of all existing populations. The variables in this study are raw materials, supporting materials, labor and equipment. The results showed a 12%/yr NPV calculation in 1%/month. At a discount factor of 1% which is equal to Rp 14.546.944. BCR of 1,16 (>1), IRR of 5% (>1%) and return on investment by calculating PP for 9,92 months, BEP units/production of 288 packages and BEP for Rp 2.486. BEP analysis had reached the break-even point that was determined, namely 1. From the five criteria used, it was indicated that the pile processing in the Kulisusu sub-district was feasible to be developed.